Esketamine for postoperative sleep disturbance: clinical evidence, mechanisms, and future directions - Liu, Qijing; Liu, Ying; Fu, Qian; Gao, Boxiong; Liu, Yatao (Frontiers in Psychiatry, 2025)
Postoperative sleep disturbance (PSD) is a common complication following surgery. Numerous factors can contribute to PSD, including personal factors, intraoperative factors, postoperative complications and environmental factors. PSD can lead to a range of adverse outcomes, severely impairing patients’ postoperative recovery and long-term prognosis. Esketamine, a non-competitive N-methyl-D-aspartate (NMDA) receptor antagonist and the dextrorotatory isomer of ketamine, which has stronger receptor affinity, more significant analgesic effects and better safety than ketamine. In recent years, in addition to the proven sedative, analgesic and antidepressant properties, emerging evidence highlights that esketamine may improve PSD through a variety of mechanisms, but the existing research results are still controversial. This article reviews the latest research progress of esketamine in improving PSD, and discusses its clinical efficacy and potential mechanism of action, in order to provide theoretical basis and practical guidance for optimizing perioperative anesthesia management and promoting postoperative rehabilitation of patients.